Congenital Bleeding Disorders Diagnosis and Management (Springer International Publishing, 2018)
This book describes in detail the clinical presentation, diagnosis, and management of a wide range of congenital bleeding disorders. It will assist readers in overcoming the significant challenges involved in clinical and laboratory diagnosis and in providing effective clinical care that makes optimal use of new products, including recombinant factor concentrate. The coverage ranges from hemophilia A and B and von Willebrand disease to rare bleeding disorders such as congenital factor V, factor X, factor XI, and factor XIII deficiency and inherited platelet function disorders. The exceptional attention to rarer conditions is of particular importance given the considerable risk of overlooking them during diagnosis, with potential consequences for disease-related morbidity and mortality. The authors are acknowledged specialists in the field from across the world who have particular expertise in the disorder that they discuss. The book will be of value to hematologists, oncologists, pediatricians, laboratory specialists and technicians, general physicians, and trainees. .